Asuhan Kebidanan Komprehensif pada Ny “N” dengan Penerapan Kompres Dingin untuk Mengurangi Nyeri Persalinan Kala 1 Fase Aktif - Rosmiarti, Rosmiarti; Salsabila, Dhea Putri (Ners Akademika, 2024)
Purpose: The purpose of the study was to analyze the effect of the remote preceptor model on clinical practice learning on improving lecturer performance. The research design used quasi-experimental (The pre-test-post-test control group design). Method: The subjects of the study were taken by purposive sampling, namely 67 lecturers from midwifery institutions. Data were analyzed using descriptive and inferential statistics, namely the Chi Square test, Wilcoxon test and Mann Whitney test, Logistic Regression test. Results: There was a difference in the assessment of lecturer performance in the treatment group after being given a remote preceptor model compared to the control group with a mean difference of 10.98 (p <0.05). The remote preceptor model in clinical practice learning improved lecturer performance 9 times to be better (OR 8.681 (IK95%; 2.884 - 26.129)). The increase in lecturer work occurred because there was effectiveness in the lecturer's time and energy so that they were able to carry out other tasks according to the Tri Dharma of higher education. Limitation: Only one case (Mrs. “N”) was included so the results cannot be generalized to a wider population. Research with a larger sample will provide more representative data. Contribution: The findings from this article may impact obstetric practice by offering additional methods that can be used to improve patient comfort during the active phase of labor.